Linking endogenous decay and sludge bulking in the microbial community to membrane fouling at sub-critical flux - Anh Q. Nguyen; Luong N. Nguyen; Md Abu Hasan Johir; Huu Hao Ngo; Long D. Nghiem (Journal of Membrane Science Letters, 2022)
This study examined membrane fouling and associated microbial taxa in a membrane bioreactor operating at a sub-critical flux condition using next-generation amplicon sequencing. The membrane was operated at a sub-critical flux, thus, fouling was not observed until endogenous decay. The observed fouling could be attributed to endogenous decay which was driven by nutrient deficiency at high sludge age and low food-to-microorganisms ratio (decreasing from 0.15 to 0.09 gBOD/gMLVSS.d). Endogenous decay resulted in a sharp decrease of the number of species and evenness between different species (49.7 and 58.9% compared to the inoculum, respectively). The release of dissolved organic matters and cell debris from endogenous decay as well as the excessive growth of filamentous bacteria, e.g. Thiotrichales were the main contributors to membrane fouling. The relative abundance of Thiotrichales significantly correlated with TMP (Pearson R = 0.996, p-value <0.001), indicating this order's contribution to membrane fouling. Other dominant orders in the mixed liquor after endogenous decay such as Rhizobiales, Burkholderiales, Rhodospirillales and Myxococcales, Flavobacteriales can produce extracellular polymeric substances and aggravating membrane fouling. Fouling layers possess highly similar microbial composition with the mixed liquor, with some filamentous microbial orders, e.g. Corynebacteriales and Oligoflexales showing increased relative abundance by 6.83 and 5.64 folds, respectively.